Biblioteka w osadzie wiejskiej Czerwieńsk w województwie zielonogórskim od 1949 do 1956 roku = The rural settlement`s library in Czerwieńsk, Zielona Góra province between 1949 and 1956 - Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The library in Czerwieńsk, Zielona Góra District was an only institution that made books available to the local community at the time it was established in 1949. The book collection, having been politicized by the Polish United Workers? Party, has made people above 20 years of age increas- ingly reluctant to use it. As a result, it was announced in April of 1956 that the number of active members was 129 people.
Keywords: Czerwieńsk - biblioteki; powiat zielonogórski; polscy komuniści; kolektywizacja; Plan 6-letni; library; Zielona Góra District; Polish communists; collectivization; six-year economic plan